Le rôle des facteurs locaux sur les effets des changements climatiques au Quaternaire supérieur sur les environnements naturel du Néguev septentrional - Aaron Yair (Physio-Géo)
Dryland areas are usually regarded as highly sensitive to climate change. A positive relationship between average annual rainfall and environmental variables is often assumed by many scientists for semi-arid and arid areas. However; existing global models are not yet capable of predicting accurately the evolution of regional climates and their possible impact on the environment. Furthermore, the global models fail to address an important issue: with decreasing average annual rainfall water resources may be highly dependant on the relationships between rainfall and surface properties which greatly influence the degree to which water will percolate or will be transformed into runoff, thereby significantly affecting the spatial redistribution of water resources. In other words, a given climate change would be expected to have differential effects in a rocky area, in a loess covered area or in a sandy area. The northern Negev area offers unique conditions for the study of the possible effects of the foreseen climate change along rainfall gradient under changing surface conditions. Two case studies are considered in the study. The first deals with the environmental effects of loess penetration into the area, during a wet climatic phase. The second considers the differential effects of biological topsoil crusts on the water regime along a rainfall gradient in a sandy area. The rainfall gradient is accompanied by other gradients (geomorphological, pedological and biological). Data obtained draw attention to the complex relationships between annual rainfall, surface properties, water availability and ecosystem structure. The parallel gradients may have negative or positive effects on water resources and environmental quality.